2020
DOI: 10.1021/acsaelm.0c00172
|View full text |Cite
|
Sign up to set email alerts
|

External Quantum Efficiency of 6.5% at 300 nm Emission and 4.7% at 310 nm Emission on Bare Wafer of AlGaN-Based UVB LEDs

Abstract: As per the Minamata Convention on Mercury, regulation on mercury use will be stricter from the year of 2020, and safe AlGaNbased ultraviolet (UV) light sources are urgently needed for killing SARS-CoV-2 (corona virus). AlGaN-based ultraviolet-B (UVB) light-emitting diodes (LEDs) and UVB laser diodes (LDs) have the potential to replace toxic mercury UV lamps. Previously, the internal-quantum-efficiency (η int ) was enhanced from 47 to 54% in AlGaN UVB multiquantum wells (MQWs). However, some nonlinear behaviors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
217
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(220 citation statements)
references
References 54 publications
3
217
0
Order By: Relevance
“…[ 43 ] It has been verified that the strain relaxation of n ‐AlGaN is crucial to the IQE of emission from quantum wells by modulating the density of dislocations, furthermore contributing to the performance of LED, for example, in UVA and UVB device. [ 44,45 ] For various kinds of AlGaN‐based LEDs with different Al compositions, a relatively low strain relaxation is preferred to achieve low TDDs. Herein, the low relaxation ratio of ≈4.2% promises a high quality of n ‐Al 0.64 Ga 0.36 N layer, which is the prerequisite to achieve the satisfied IQE as high as 60%.…”
Section: Resultsmentioning
confidence: 99%
“…[ 43 ] It has been verified that the strain relaxation of n ‐AlGaN is crucial to the IQE of emission from quantum wells by modulating the density of dislocations, furthermore contributing to the performance of LED, for example, in UVA and UVB device. [ 44,45 ] For various kinds of AlGaN‐based LEDs with different Al compositions, a relatively low strain relaxation is preferred to achieve low TDDs. Herein, the low relaxation ratio of ≈4.2% promises a high quality of n ‐Al 0.64 Ga 0.36 N layer, which is the prerequisite to achieve the satisfied IQE as high as 60%.…”
Section: Resultsmentioning
confidence: 99%
“…The moderately doped p‐MQB EBL was used to achieve better hole transport to enhance the hole injection toward the MQWs as well as prevent the high‐energy electron from overshooting. [ 16 ] The influence of excimer laser annealing (ELA) on the activation of Mg dopants and on the suppression of unwanted impurities such as H, C, and O as well as on the annihilation of the localized energy state in the p‐ALGaN hole source layer (HSL) was reported. After ELA treatment, the GaN bonding ratio is reduced and GaO, as well as GaGa bonding ratios in the p‐AlGaN HSL, are increased.…”
Section: Introductionmentioning
confidence: 99%
“…The theory has been proved to be effective in both blue and DUV LEDs with graded p-type AlGaN layer [19]- [23]. In addition, some researchers found that by taking advantage of the tunneling process, the conventional thermionic emission process limited by the potential barrier can be bypassed and thus the hole injection efficiency can be boosted effectively [12], [24], [25]. Furthermore, we reported that the hole injection of blue LEDs can be boosted by introducing a series of shallow wells in the valence band with an InGaN/GaN superlattice layer [26].…”
Section: Introductionmentioning
confidence: 99%